Regional Tax Management from the Perspective of Social Justice and Accountability - Erni Yusnita Siregar; Yusril Mahendra; Zenni Khairani Putri; Aulia Rizki Pulungan; Batara Doli; Anisah Zahara; Wahyu Muhammad (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
This study aims to analyze regional tax management from the perspective of social justice and accountability. Regional taxes are a primary source of Regional Original Income (PAD) and play a crucial role in financing development and public services. However, in practice, regional tax management still faces various obstacles, such as low taxpayer compliance, a lack of transparency, and weak oversight. This study used a qualitative approach with library research, analyzing various relevant literature sources, such as scientific journals, books, and official documents. The results indicate that social justice and accountability are two key interrelated principles in regional tax management. Social justice emphasizes the proportional distribution of the tax burden according to community capacity, while accountability emphasizes government transparency and accountability in managing tax funds. The implementation of these two principles can increase public trust and encourage taxpayer compliance. Therefore, improvements are needed through digitalization of the tax system, strengthening oversight, and developing policies oriented toward social justice. Thus, regional tax management is expected to be effective, fair, and accountable.